Clarifying the mechanisms of the light-induced color formation of apple peel under dark conditions through metabolomics and transcriptomic analyses - Xue, Xiaomin; Tian, Shoule; Chen, Ru; Han, Xueping; Wang, Jinzheng; Zhao, Xianyan (Frontiers in Plant Science, 2022)
Many studies have demonstrated that anthocyanin synthesis in apple peel is induced by light, but the color of bagged apple peel continues to change under dark conditions after light induction has not been characterized. Here, transcriptional and metabolic changes associated with changes in apple peel coloration in the dark after different light induction treatments were studied. Apple pericarp can achieve a normal color under complete darkness followed by light induction. Metabolomics analysis indicated that the expression levels of cyanidin-3-O-galactoside and cyanidin-3-O-glucoside were high, which might be associated with the red color development of apple peel. Transcriptome analysis revealed high expression levels of MdUFGTs, MdMYBs, and MdNACs, which might play a key role in light-induced anthocyanin accumulation under dark conditions. 13 key genes related to dark coloring after light induction were screened. The results of this study provide new insights into the mechanism of anthocyanin synthesis under dark conditions.